ANTESENDEN DARI KEPUASAN PENGGUNA TELEPON SELULER MERK VIVO DI MADIUN - Kadi, Dian Citaningtyas Ari; Setyanta, Budi (LP2M Institut Teknologi dan Bisnis Asia Malang, 2021)
ABSTRACT This study aims to determine the impact of product quality, price perception, and country of origin on user satisfaction of the Vivo cellular phone in Madiun. The number of samples in this study was 100 taken through convenience technique using an online questionnaire. The research hypothesis was tested using multiple linear regression. The results showed that the research model met the requirements of the goodness of fit. Product quality, price perception, and country of origin affect user satisfaction for the Vivo brand mobile phone in Madiun. Future research can add other variables to improve the ability of the research model to explain customer satisfaction. Keywords: Product Quality, Price Perception, Customer Satisfaction, Country of Origin